Criticism: Synthesis of Empiricism-Rationalism and Its Implications for Islamic Family Law Studies - Hurnawijaya, Hurnawijaya - (Hukum Keluarga Islam, 2023)
Abstract The idea of ​​criticism which synthesizes rationalism and empiricism was coined by Immanuel Kant (1724-1804) in the 18th century. A century known as the aufklarung era (English: Enlightenment), because humans began to realize that the source of knowledge and truth was not only obtained from the authority of religious institutions (churches, mosques, etc.), interpreters of religious texts, religious groups or wise people. , but can be found for those who realize the error (experience), then start thinking activities. By using a qualitative analysis approach to the literature study model (literature study) with content analysis, this research aims to reveal the synthesis between rationalism and empiricism in the philosophical school pioneered by Emanuel Kant and its implications for the study of Islamic Family Law. The results of this research show that the synthesis of two types of theses - rationalism vis a vis empiricism - is what made Immanuel Kant famous as a philosopher with the manifestation of critical philosophy (criticism). According to Kant, only leaning towards one of the methods of searching for the source of truth, namely rationalism or empiricism, will fall into the weakness of knowledge and damage to the standards of truth in knowledge. In order to find the ultimate truth, Kant offers two formulas called a priori and a posteriori which will be synthesized into a formula that complements each other in a coherent way. Thoughts and studies regarding the synthesis of these two schools are an interesting study to describe, especially if they are related to how they relate to several aspects of life, including the study of Islamic Family Law as part of socio-religious studies. Keywords: Synthesis, Rationalism, Empiricism, Criticism, Islamic Family Law.